2022
DOI: 10.1108/ijdi-12-2021-0265
|View full text |Cite
|
Sign up to set email alerts
|

The effects of IMF programs on income inequality: a semi-parametric treatment effects approach

Abstract: Purpose This paper aims to provide new insights regarding the impact of International Monetary Fund (IMF) programs on income inequality. Design/methodology/approach The paper uses a novel methodological approach proposed by Acemoglu et al. (2019), using (1) the regression adjustment, (2) the inverse probability weighting and (3) the doubly robust estimator, which combines (1) and (2), and a sample of annual data for 135 developing countries over the time period 1970 to 2015. Findings The findings show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, low inflation strengthens the income-equalizing effect of fiscal redistribution. Chletsos and Sintos (2023) [ 30 ] proposed that the overall impact of financial development on income inequality averages to zero but varies systematically based on study characteristics. In contrast, Chletsos and Sintos (2022) [ 31 ] found that IMF programs are associated with increased income inequality for up to five years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, low inflation strengthens the income-equalizing effect of fiscal redistribution. Chletsos and Sintos (2023) [ 30 ] proposed that the overall impact of financial development on income inequality averages to zero but varies systematically based on study characteristics. In contrast, Chletsos and Sintos (2022) [ 31 ] found that IMF programs are associated with increased income inequality for up to five years.…”
Section: Literature Reviewmentioning
confidence: 99%